Language Teacher Leadership in Developing Learning Progressivity Based on Conceptual and Instructional Capacities - Khirjan Nahdi (Universitas Hamzanwadi, 2022)
This article aims to identify the level of leadership of language teachers in developing students' learning progress based on conceptual and didactic qualities. This goal is achieved by answering the following questions: 1) the level of quality of concepts related to the progress of student learning; and 2) administrative components and educational processes. Question (1) was introduced with data from code A and question (2) was introduced with data from codes B and C. Data was collected through a survey of educational agendas using concept quality, management, and multi rate indicators. Analyzes were performed by describing regression data. The results of this study indicate that respondents have a good idea of their students' learning progress. A conceptual understanding of learning progression is inversely related to quality of learning and instructional management. Respondents continue to predominate as a motivator to achieve their learning goals through encouragement and guidance. On the other hand, they are still weak as moderators, designers, and initiators of learning objectives. A paradigm shift is needed in the teacher-student relationship.